Breaking news: examining teachers’ perceptions and pedagogy of global current events - Brown, James Scott (My University, 2025)
In today’s classrooms, teachers and students can use global current events to constantly reexamine the world and their place within it, and address complex issues such as international relations, economic inequality, and effects of globalization. However, while these topics are discussed in many classes in the United States, the specific practices utilized, and global current events topics chosen remain largely a teacher’s personal choice. Though there has been advocacy centering on the ways in which teachers may approach global current events, answers to important questions, including how teachers approach the teaching of global current events topics, how global current events can serve as a means for promoting elements of global education, and what factors contributed to teachers’ willingness to focus on global current events topics in their respective classrooms remain unknown. This study aimed to address each of these questions and explore the goals of global current events education within the larger framework of global education and social justice by using a qualitative approach in the conduct of interviews, classroom observations and an elicitation task. As a result of this study, three themes emerged regarding the teaching of global current events: implementation, positionality, and self-selection. Findings from this study indicate that while each of the teachers viewed themselves as global educators and advocated for the teaching of global current events in their social studies classrooms, these lessons were often limited to use as procedural tasks due to constraints of time, administrative oversight, and external pressures. Furthermore, when seen through lens of two theoretical frameworks, the findings of this study suggest that the teaching of global current events can potentially serve as a means to actualize global competence or social justice, but need additional resources, time, and training to do so. The dissertation concludes with a set of curricular implications and suggestions, citing the importance of balancing the teaching of global current events with the scripted curriculum and highlighting individual strategies teachers can use to support visions of global competence and social justice in the classroom.
Keywords: Global current events; Global competence; Social justice; Secondary education; Social studies; Teacher perception